In Vivo NADH/NAD+ Biosensing Reveals the Dynamics of Cytosolic Redox Metabolism in Plants. Issue 10 (13th October 2020) - Steinbeck, Janina; Fuchs, Philippe; Negroni, Yuri L.; Elsässer, Marlene; Lichtenauer, Sophie; Stockdreher, Yvonne; Feitosa-Araujo, Elias; Kroll, Johanna B.; Niemeier, Jan-Ole; Humberg, Christoph; Smith, Edward N.; Mai, Marie; et al.
Abstract : In planta NAD redox monitoring using a fluorescent protein sensor delivers insight into the in vivo dynamics of plant cytosolic redox metabolism. Abstract: NADH and NAD + are a ubiquitous cellular redox couple. Although the central role of NAD in plant metabolism and its regulatory role have been investigated extensively at the biochemical level, analyzing the subcellular redox dynamics of NAD in living plant tissues has been challenging. Here, we established live monitoring of NADH/NAD + in plants using the genetically encoded fluorescent biosensor Peredox-mCherry. We established Peredox-mCherry lines of Arabidopsis ( Arabidopsis thaliana ) and validated the biophysical and biochemical properties of the sensor that are critical for in planta measurements, including specificity, pH stability, and reversibility. We generated an NAD redox atlas of the cytosol of living Arabidopsis seedlings that revealed pronounced differences in NAD redox status between different organs and tissues. Manipulating the metabolic status through dark-to-light transitions, respiratory inhibition, sugar supplementation, and elicitor exposure revealed a remarkable degree of plasticity of the cytosolic NAD redox status and demonstrated metabolic redox coupling between cell compartments in leaves. Finally, we used protein engineering to generate a sensor variant that expands the resolvable NAD redox range. In summary, we established a technique for in planta NAD redox monitoring to deliver important insight into the in vivo dynamics of plant cytosolic redox metabolism.